Enhancing Infrared Photoluminescence Performance via Li+ Substitution and Yb3+ Codoping in Na3ScSi3O9:Cr3+ Phosphor - Zhuanzhuan Zhang; Yanjie Liang (Crystals, 2023)
Cr3+-doped broadband infrared luminescent materials have attracted growing attention in consideration of their potential applications in phosphor-converted infrared light sources. However, discovering infrared-emitting luminescent materials with ultrabroadband emission and excellent thermal stability still remains a challenge. In this work, we report the significant improvement of infrared photoluminescence properties in Na3ScSi3O9:Cr3+ phosphor via Li+ substitution and Yb3+ codoping. The prepared Na3ScSi3O9:Cr3+ phosphor can produce broad infrared emission over 650–1350 nm with a peak maximum at 898 nm under the excitation of blue light. Through the substitution of Li+ for Na+, the maximum infrared emission peak can be tuned from 898 nm to 850 nm. When the Li+ content is 0.5, the integrated infrared luminescence intensity of the obtained Na2.5Li0.5ScSi3O9:Cr3+ phosphor increases by 4.2 times compared with that of the Na3ScSi3O9:Cr3+ phosphor, and the luminescence thermal stability is also improved significantly (58.5%@100 °C). Moreover, Yb3+ codoping can simultaneously realize the characteristic infrared luminescence of Cr3+ and Yb3+, resulting in a broadened spectral width due to efficient energy transfer from Cr3+ to Yb3+. Finally, an ultrabroadband infrared light-emitting diode prototype is fabricated through a combination of the optimized Na2.5Li0.5ScSi3O9:2%Cr3+,0.5%Yb3+ phosphor with a commercial 490 nm LED chip, giving an infrared output power of 5.2 mW at 320 mA drive current. This work provides an effective way to optimize the infrared photoluminescence performance of Cr3+-doped Na3ScSi3O9 infrared phosphors.